Estudo do uso de barras de transferência de comprimentos reduzidos em pavimentos rígidos de concreto autoadensável - REIS, Fábio Gonçalves dos (2009)
The use of concrete pavements in highways is a valuable alternative to obtain a surface with high durability and low maintenance. This type of pavement has the performance compromised by fissures, especially when they occur in the joint with greater vulnerability of the concrete pavement. This work presents a study of the effectiveness of sawed joints in concrete pavements where eleven plates were tested until failure. The variables were: length of circular dowels (200 mm, 300 mm, 400 mm and 500 mm), dowel diameter (10 mm and 16 mm) and type of concrete (conventional and self-compacting). The tests were performed on the concrete plates supported on a base composed of sheets of rubber. A line load was placed on one side of the joint. The test results showed that the use of transfer dowels contributes significantly to the efficiency of the concrete pavements and increasing the length and the diameter of the circular dowels improves efficiency; 10 mm diameter dowels are not compatible with 120 mm thick concrete pavements, but 16 mm dowels bars present good performance; the use of reduced dowel bar lengths below 40 mm is not recommended; pavements with conventional concrete have better performance in the joints due to better aggregate interlocking that the conventional concrete of this search present, when compared the self-compacting concrete; dowels bars with reduced length did not reach yielding, characterizing an incomplete use of steel dowels because the transfer energy its over before the yielding of steel dowels